네트워크 취약성 분석을 위한 확장된 사이버 공격 트리에 관한 연구 - 엄정호; 박선호; 정태명; Eom, Jung Ho; Park, Seon Ho; Chung, Tai M ((사)디지털산업정보학회 논문지, 6(3), 2010)
We extended a general attack tree to apply cyber attack model for network vulnerability analysis. We defined an extended cyber attack tree (E-CAT) which extends the general attack tree by associating each node of the tree with a transition of attack that could have contributed to the cyber attack. The E-CAT resolved the limitation that a general attack tree can not express complex and sophisticate attacks. Firstly, the Boolean expression can simply express attack scenario with symbols and codes. Secondary, An Attack Generation Probability is used to select attack method in an attack tree. A CONDITION-composition can express new and modified attack transition which a aeneral attack tree can not express. The E-CAT is possible to have attack's flexibility and improve attack success rate when it is applied to cyber attack model.